Ethical consideration in patients with obesity - Permatasari, Dian (World Nutrition Journal, 2024)
Obesity is an epidemic that is about to overwhelm the economic and health care structures of society. Obesity is a complex medical condition that has roots in genetic, environmental and social exposures that should not be attributed lack of willpower any more than other diseases. One in five adults, one in five children aged 5-12, and one in seven adolescents aged 13-18 in Indonesia are overweight or obese, according to estimates from the 2018 National Basic Health Research survey